2013
DOI: 10.5194/hessd-10-13707-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Palaeo-modeling of coastal salt water intrusion during the Holocene: an application to the Netherlands

Abstract: Abstract. Management of coastal fresh groundwater reserves requires a thorough understanding of the present-day groundwater salinity distribution and its possible future development. However, coastal groundwater often still reflects a complex history of marine transgressions and regressions, and is only rarely in equilibrium with current boundary conditions. In addition, the distribution of groundwater salinity is virtually impossible to characterize satisfactorily, complicating efforts to model and predict co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Delsman et al . [] notes that coastal groundwater reserves are rarely in equilibrium with current boundary conditions, which greatly complicates modeling the distribution of water salinities. The current groundwater condition of coastal aquifer systems must be explored in light of the historical development of groundwater salinity in combination with present day hydrological processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Delsman et al . [] notes that coastal groundwater reserves are rarely in equilibrium with current boundary conditions, which greatly complicates modeling the distribution of water salinities. The current groundwater condition of coastal aquifer systems must be explored in light of the historical development of groundwater salinity in combination with present day hydrological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Varying sediment supply rates, tectonic activity, river avulsions, basin subsidence, eustatic sea level change, and anthropogenic alterations have all influenced aquifer construction and groundwater chemistry. Delsman et al [2013] notes that coastal groundwater reserves are rarely in equilibrium with current boundary conditions, which greatly complicates modeling the distribution of water salinities. The current groundwater condition of coastal aquifer systems must be explored in light of the historical development of groundwater salinity in combination with present day hydrological processes.…”
Section: 1002/2014wr016262mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies dealing with the latter set the landward boundary less than 200km from the coastline even in deltaic areas (Delsman et al 2013;Larsen et al 2017;Nofal et al 2016). Similarly, previous studies showed that submarine groundwater discharge can occur more than 100km offshore (Kooi & Groen 2001;Post et al 2013).…”
Section: Sediment Thickness Estimation 20mentioning
confidence: 99%